Reforming Water Law and Governance From Stagnation to Innovation in Australia (Springer Singapore, 2018)
This book identifies the most effective water policy tools and innovations, and the circumstances that foster their successful implementation by taking a comparative look at a world-leading 'laboratory' of water law and governance: Australia. In particular, the book analyses Australia's 20-year experience implementing a hybrid governance system of markets, hierarchical regulation, and collaborative integrated water planning. Australia is acknowledged as a world leader in water governance reform, and an examination of its relatively mature water law and governance system has great significance for many international academics and jurisdictions. This book synthesises practical lessons and theoretical insights from Australia, as well as recommendations from comparative analysis with countries such as the United States to provide useful guidance for policymakers and scholars seeking to apply water instruments in a wide range of policy contexts. The book also advances our understanding of water and broader environmental governance theory and is a valuable reference for scholars, researchers and students working in law, regulation and governance studies - especially in the field of water and environmental law.